Asas Pemaafan Hakim dalam Pembaharuan Hukum Pidana di Indonesia - Muh. Iksan Putra Kai; Dian Ekawaty Ismail; Suwitno Yutye Imran (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out what the judge's forgiveness policy (rechterlijk pardon) is in the New Criminal Code, to find out how the rechterlijk pardon formulation in the Dutch Criminal Code compares and to find out what the challenges of rechterlijk pardon (judge's forgiveness) will be in the future. The research method used is juridical-normative with a statutory approach and a case approach. The research results show that Rechterlijk Pardon puts a different concept in giving space to judges in handing down guilty decisions without criminal penalties. Before being ratified, the principle of judge forgiveness was already used in several countries, for example the Netherlands. Even judges in Indonesia have made several decisions that contain the value of the judge's forgiveness. In connection with the analysis of Rechterlijk Pardon's challenges, it is viewed from the perspective of law enforcement and legal culture in society.